CONCEPTUALISATION OF ACADEMIC STAFF’S DIDACTIC PRACTICES IN THE CONTEXT OF PROFESSIONALISATION - Jatkauskienė, Birutė; Acienė, Elvyra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article presents a theoretical discourse of academic staff’s didactic practices with a particular emphasis on importance of conceptualisation of their didactic practices in the professionalisation context. The authors analyse the essence of didactic practice conceptualisation studies and their contribution to the professionalisation process, disclose the interrelations of conceptualisation of didactic practices and lecturers’ professional behaviour, their role-playing and models of didactic practices, that are oriented to the study process organisation, planning programmes, modules and classes, a search of information transmittal forms, the use of advanced teaching methods, as well as student counselling and communication. On the basis of the didactic practice conceptualisation studies, the authors argue that the analysis of conceptualisation of lecturers’ didactic practices and their professional behaviour (performance models, roles) can be helpful in adding missing elements to the professionalisation of academic staff and suggest strategies for professional development.